Evidence from the virobacterial agglutination test for the existence of eight serogroups of cocoa swollen shoot virus - Hughes, J.; Adomako, D.; Ollennu, L.A. (Wiley, 1995)
Many isolates of cocoa swollen shoot virus (CSSV) have been found in Ghana. Relationships between these isolates have been based on symptom expression and limited serological information. This paper reports on the serological relationships between 44 accessions of CSSV using the virobacterial agglutination test. The CSSV group is differentiated into eight groups using seven antibody 'types'. The largest group comprising those isolates closely related to CSSV 1A is sub‐divided into four further groups. These groupings are compared with previous results. Differences are seen between accessions of the same isolate which may be due to contamination of the source plants. These serological results can be used for studying mixed isolate infections as well as for determining the most closely related CSSV mild isolate for appropriate cross‐protection against severe isolates.